2021
DOI: 10.3390/molecules26092523
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Bactericidal Effects of Cold Atmospheric-Pressure Microplasma and Plasma Jet

Abstract: The direct and indirect bactericidal effects of dielectric barrier discharge (DBD) cold atmospheric-pressure microplasma in an air and plasma jet generated in an argon-oxygen gas mixture was investigated on Staphylococcus aureus and Cutibacterium acnes. An AC power supply was used to generate plasma at relatively low discharge voltages (0.9–2.4 kV) and frequency (27–30 kHz). Cultured bacteria were cultivated at a serial dilution of 10−5, then exposed to direct microplasma treatment and indirect treatment throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 46 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, plasma‐activated water expands the bacterial inactivation area to a greater extent than the electrode's cross‐sectional area, so the use of direct and indirect ACP could have synergistic antibacterial effects (Yahaya et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, plasma‐activated water expands the bacterial inactivation area to a greater extent than the electrode's cross‐sectional area, so the use of direct and indirect ACP could have synergistic antibacterial effects (Yahaya et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the inner area of onion leaves mainly was exposed to plasma-activated water, and so weaker antimicrobial activity of plasma was applied on the inner area. Nevertheless, plasma-activated water expands the bacterial inactivation area to a greater extent than the electrode's cross-sectional area, so the use of direct and indirect ACP could have synergistic antibacterial effects (Yahaya et al 2021).…”
Section: Acp Effect On Survival Pattern Of Spring Onion Leaves' Natur...mentioning
confidence: 99%
“…CINOGY GmbH Plasma Derm DBD, AdtecSteriPlas ® DBD [ 31 ] and MED NTPJ [ 29 ] are IIa medical devices that have been certified by CE in Germany. Cold plasma technology has been extensively used in the fields of sterilization [ 18 , 32 ], blood coagulation [ 33 ], inactivated vaccine preparation [ 20 ], biofunctionalized materials [ 34 , 35 , 36 ], and oral treatment [ 4 ]. In addition, low-intensity cold plasma treatment administered over a short period of time can successfully promote cell proliferation activity; therefore, it is used to promote angiogenesis, tissue vascularization, wound healing, skin repair, and tissue regeneration.…”
Section: Application Of Cold Plasma Treatment In Biomedical Fieldsmentioning
confidence: 99%
“…In addition to its application in biomedical fields, cold plasma is also mainly used, at present, in the processes of sterilization [ 18 ], biological purification [ 19 ], vaccine production [ 20 ], and food processing [ 21 ]. Our previous studies showed that appropriate cold plasma treatment promoted the development of chicken embryos [ 22 ], the growth rate of chickens and the reproductive performance of roosters [ 23 , 24 , 25 , 26 ], and affected the proliferation of Sertoli cells in chicks [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma medicine is an exciting field where life science and physics intersect. The ability to produce a cold plasma at atmospheric pressure, which is characterized by a multitude of charged particles, reactive gaseous species, electric current, and ultraviolet rays, has been the basis for the fast growth of plasma-related application areas in biomedicine [30]. Plasma can be used in oncology or cancerology; it has been demonstrated that plasma causes apoptosis or programmed physiological cell death of tumor cells as well as reducing skin tumors [31].…”
Section: Plasma Medicinementioning
confidence: 99%